Reducing emissions and metallic content of brake wear particles using alumina-coated brake discs - Cai, Ran; Nie, Xueyuan; Rosén, Martin Ek ; 0000-0002-5705-8495; Lyu, Yezhe ; 0000-0001-7560-6232; Wahlström, Jens ; 0000-0003-0696-7506 (Materials Today Communications, 2025)
Brake particle emissions present significant risks to human health, particularly when they contain metallic fine particles, which can induce oxidative stress, disrupt cellular structures, and cause genetic damage. In this study, an alumina coating was deposited on cast iron discs and a non-asbestos organic (NAO) pad and a low-metallic (LM) pad (as reference) were used as counterparts of the brake tribological coupling. While the NAO pad was less abrasive to cast iron disc than a LM brake pad, the alumina coating was to minimize the metallic content of emitted fine particles by avoiding a direct frictional contact of the pad to cast iron substrate. An airborne particle emission measurement system provided a tool for investigation of particle number concentration and particle size distribution generated from the NAO brake pad against either the coated or uncoated cast iron discs. The friction performance and weight loss of the discs and pad materials were also measured. The results indicated that the coated discs experienced almost no weight loss, whereas the weight loss of the coupling pad was initially high but eventually approaching the same level as that of the uncoated discs after the wear tracks became smoother. Although the particle size distribution remained similar, the alumina coating substantially reduced particle number concentration when the steady state of the tests was in place. The scanning and transmission electron microscopy (SEM/TEM) analysis of collected particles confirmed that metallic iron content was almost eliminated in emitted particles. Additionally, a smoother friction surface was found to further reduce the brake wear. A longer running time of the brake coupling can reduce surface roughness of alumina-coated discs but increase the surface roughness of uncoated discs, highlighting the long-term benefits of alumina coatings in mitigating brake wear and particle emissions.
Publisher Copyright: © 2025
Keywords: Brake disc; Coating; Particle emission; Wear